Analysis of High Temperature Oxidation Characteristic of Chrome-Plated, Nickel-Plated and Non-Plated Mild Steels - Alemayehu, Atalay; Beyene, Eaba; Batu, Temesgen; Tirfe, Dagim (Advances in Mechanical and Materials Engineering, 2023)
Metals are the best engineering materials owing to their superior conductivity, mechanical properties, and formability. However, they can be highly affected by environmental elements like oxygen, chlorine, etc. This reaction of metals with the environmental elements will indeed alter their electrical, chemical, and mechanical properties. To protect against corrosion, various protection methods such as electroplating have been established. The presence of anodic or cathodic films on the substrate surface protects steel from corrosion damage at ambient atmospheric temperature. This work focuses on the effect of temperature on the oxidative (corrosion) rate of non-plated, nickel-plated, and chrome-plated ASTM A283GC mild steel samples. A temperature range of 200–800 °C and a total heating time of 120 min were considered in this experiment. A temperature-regulated muffle furnace with a maximum heating capacity of 1000 °C has been used. Weight changes were determined every 30 minutes of heating using a digital weight balance with a precision of 0.001 g. The obtained experimental results of non-plated, nickel-plated, and chrome-plated mild steel samples were analyzed and compared with each other. The effect of oxidation on the surface hardness has also been studied with the help of a Vickers hardness testing machine. Changes in the physical nature of the samples caused by oxidation were also observed and pictured using a camera.